The Effect of Implementing A Learning Management System on Student Motivation and Satisfaction Levels - Murcahyanto, Hary (IJE : Interdisciplinary Journal of Education, 2024)
This study aims to determine the influence of the Learning Management System (LMS) on students' motivation and satisfaction levels. The research method used is quantitative with an associative approach. The study involves 60 students as subjects. The research technique employs simple random sampling with data collection conducted through questionnaires. Data analysis is performed using SPSS version 16. The results of the study indicate a positive and significant influence of LMS on students' learning motivation. Based on the significance test, the calculated t-value (4.382) > t-table (1.67155) for Y1 (learning motivation), which means Ho1 is rejected and Ha1 is accepted. The study also shows a positive and significant influence of LMS on students' satisfaction levels, with a calculated t-value (5.406) > t-table (1.67155), which means Ho1 is rejected and Ha1 is accepted. The conclusion of this study is that learning using LMS has a significant impact on students' motivation and satisfaction levels.